Using artificial intelligence to develop a measure of orthopaedic treatment success from clinical notes - Floyd, Sarah B.; Almeldien, Ahmed G.; Smith, D. Hudson; Judkins, Benjamin; Krohn, Claire E.; Reynolds, Zachary Cole; Jeray, Kyle; Obeid, Jihad S. (Frontiers in Digital Health, 2025)
IntroductionA readily available outcome measure that reflects the success of a patient's treatment is needed to demonstrate the value of orthopaedic interventions. Patient-reported outcome measures (PROMs) are survey-based instruments that collect joint-specific and general health perceptions on symptoms, functioning, and health-related quality of life. PROMs are considered the gold standard outcome measure in orthopaedic medicine, but their use is limited in real-world practice due to challenges with technology integration, the pace of clinic workflows, and patient compliance. Clinical notes generated during each encounter patients have with their physician contain rich information on current disease symptoms, rehabilitation progress, and unexpected complications. Artificial intelligence (AI) methods can be used to identify phrases of treatment success or failure captured in clinical notes and discern an indicator of treatment success for orthopaedic patients.MethodsThis was a cross-sectional analysis of clinical notes from a sample of patients with an acute shoulder injury. The study included adult patients presenting to a Level-1 Trauma Center and regional health system for an acute Proximal Humerus Fracture (PHF) between January 1, 2019 and December 31, 2021. We used the progress note from the office visit for PHF-related care (ICD10: S42.2XXX) or shoulder pain (ICD10: M45.2XXX) closest to 1-year after the injury date. Clinical notes were reviewed by an orthopaedic resident and labeled as treatment success or failure. A structured comparative analysis of classifiers including both machine and deep learning algorithms was performed.ResultsThe final sample included 868 clinical notes from patients treated by 123 physicians across 35 departments within one regional health system. The study sample was stratified into 465 notes labeled as treatment success and 403 labeled as treatment failure. The Bio-ClinicalBERT model had the highest performance of 87% accuracy (AUC = 0.87 ± 0.04) in correctly distinguishing between treatment success and failure notes.DiscussionOur results suggest that text classifiers applied to clinical notes are capable of differentiating patients with successful treatment outcomes with high levels of accuracy. This finding is encouraging, signaling that routinely collected clinical note content may serve as a data source to develop an outcome measure for orthopaedic patients.